Pre‐exposure prophylaxis: awareness, acceptability and risk compensation behaviour among men who have sex with men and the transgender population. Issue 4 (27th November 2017) - Uthappa, CK; Allam, RR; Pant, R; Pal, S; Dinaker, M; Oruganti, G; Yeldandi, VV
Abstract : Objectives: This exploratory study examined the facilitators of and barriers to acceptance of pre‐exposure prophylaxis (PrEP) and potential risk compensation behaviour emerging from its use among men who have sex with men (MSM) and transgender individuals (TGs) in India. Methods: A questionnaire was administered to 400 individuals registered with a targeted intervention programme. Logistic regression models were used to identify facilitators of and barriers to PrEP acceptance. Results: The respondents consisted of 68% MSM and 32% TGs. Risk behaviour categorization identified 40% as low risk, 41% as medium risk and, 19% as high risk for HIV infection. About 93% of the respondents were unaware of PrEP, but once informed about it, 99% were willing to use PrEP. The facilitators of PrEP acceptance were some schooling [odds ratio (OR) 2.16; P = 0.51], being married or in a live‐in relationship (OR 2.08; P = 0.46), having a high calculated risk (OR 3.12; P = 0.33), and having a high self‐perceived risk (OR 1.8; P = 0.35). Increasing age (OR 2.12; P = 0.04) was a significant barrier. TGs had higher odds of acceptance of PrEP under conditions of additional cost (OR 2.12; P = 0.02) and once‐daily pill (OR 2.85; P = 0.04). Individuals identified as low risk for HIV infection showed lower odds of potential risk compensation, defined as more sexual partners (OR 0.8; P = 0.35), unsafe sex with new partners (OR 0.71; P = 0.16), and decreased condom use with regular partners (OR 0.95; P = 0.84), as compared with medium‐risk individuals. The associations, although not statistically significant, are nevertheless important for public health action given the limited scientific evidence on PrEP use among MSM and TGs in India. Conclusions: With high acceptability and a low likelihood of risk compensation behaviour, PrEP can be considered as an effective prevention strategy for HIV infection among MSM and TGs in India.